Relationship between forest void structure and microclimate - SETOGUCHI, Hiroaki; NAKAJIMA, Fumio; KATO, Akira; UEHARA, Koichi; AOYAGI, Kantaro (Journal of the Japanese Society of Revegetation Technology, 2024)
This study evaluated the impact of the “void”, a non-tangible space in the forest, on the microclimate, rather than tangible objects such as trees and understory vegetation. A terrestrial laser was used to measure the forest void space in three dimensions and compact meteorological sensors were used to measure the temperature and humidity inside the forest. The relationship between the number of voxels for the tangible and non-tangible objects showed that the distribution of forest void structure was different by different height layer. The correlation analysis between the number of voxels and meteorological data showed that forest voids have a significant influence on minimum temperature. The previous study showed the presence or absence of forest canopy influences microclimate, however this study shows the relationships between forest structure and microclimate was obtained from the spatial distribution of forest void.